"Neurodevelopmental outcome of a child with UPD(16)mat: A case report" - Maria Novelli; Valeria Mammarella; Francesca Calandriello; Sara Temofonte; Marina Goldoni; Ilaria Macchiarulo; Paolo Versacci; Antonio Pizzuti; Jessica Petrilli; Carlo Di Brina; Barbara Caravale (Elsevier, 2024)
Objective: UPD(16)mat is a rare genetic condition characterized by intrauterine growth deficiency and multiple congenital malformations. To the best of our knowledge, neurodevelopmental disorders have never been described in association with UPD(16)mat, nor a comprehensive neuropsychological profile of a UPD(16)mat child has never been delineated. We present a young patient diagnosed with UPD(16)mat, and provide clinical description, comprehensive neurodevelopmental, neuropsychological and neurological assessment. Method: Neuropsychological examination included global neurodevelopment and intelligence scales, as well as specific trials for gross-motor, fine-motor and perceptual motor abilities, and language skills. Results: The patient shows multiple congenital anomalies, including oesophageal atresia, mild bone alterations, hypospadias, persistent left superior vena cava. The neurodevelopmental evaluation demonstrates a speech disorder, signs of gross and fine motor skills difficulties, balance and visuo-motor deficit. Conclusion: Evidence from this study indicates that UPD(16)mat may present neuropsychological and/or minor neurological abnormalities. Monitoring both the early and late neurodevelopmental outcomes during childhood is recommended for the chance of an early intervention.